Expendable Missiles vs. Reusable Platform Costs and Historical Data - Hamilton, Thomas (RAND Corporation, 2012)
This report uses an analysis of historical use of air-to-ground attacks during and since the Vietnam war to assess the economic wisdom of relying primarily on expendable weapons, such as cruise missiles. Such exclusive reliance only makes economic sense if all possible conflicts over the system lifetime can be ended in a total of less than about ten days.